Effect of sequential twin screw extrusion and fungal pretreatment to release soluble nutrients from soybean residue for carotenoid production - Lee, Jaslyn Jie Lin (2020)
Background: Soybean residue (okara) is an agricultural by‐product, which is rich in protein and fiber. This study evaluated a novel sequential process which combined fungal pretreatment (F) and twin screw extruder (E), to hydrolyze okara. The sequence of the pretreatment steps, and extruder at screw speeds 200 rpm (200) or 600 rpm (600), were tested. Next, soluble nutrients were extracted to create Fokara, EFokara200, EFokara600, FEokara200 and FEokara600 okara media.Results: All the prepared okara media could support the growth and carotenoid production by the yeast Rhodosporidium toruloides. This suggested that okara proteins and polysaccharides were successfully hydrolyzed by extrusion and fungal pretreatment, into soluble nutrients. Rhodosporidium toruloides accumulated the highest biomass of 23.7 mg mL−1 dry cell weight (DCW), when grown on FEokara600 media. This was higher as compared to commercial YPG (yeast extract–peptone–glycerol) media (18.7 mg mL−1 DCW). However, R. toruloides accumulated the highest carotenoid production of 13.2 µg mL−1 when grown on EFokara200 media as the nutrient source. This was comparable to carotenoid production of 13.1 µg mL−1 when R. toruloides was grown on YPG media. Conclusion: Extrusion in combination with fungal pretreatment, is a low cost process, to hydrolyze and re‐use okara, for carotenoid production.